샤르코 관절병증으로 오인하였던 거주상 관절의 골결핵 환자의 치료: 증례 보고 - 김성욱; 박재욱; 박현우; Sung-Wook Kim; Jae-Wook Park; Hyun-Woo Park (대한족부족관절학회지, 2025)
Cases of bone tuberculosis in the foot are very rare. The clinical symptoms are nonspecific, and the radiology findings may resemble those of stress fractures or septic arthritis, making early diagnosis difficult. This paper reports a case of bone tuberculosis involving the talonavicular joint and the approach to diagnosis and treatment.